The God Letter Albert Einstein. Ateisme Ilmiah: Meyakinkan? Albert Einstein's God Letter. Is Scientific Atheism Convincing? - Magnis-Suseno, Franz (STF Driyarkara - Diskursus, 2025)
This article questions Einstein’s famous statement that God is just the expression of human weakness and that religion is nothing more than a primitive superstition. The author agrees that the development of the universe should, indeed, be explained by laws of nature, without any recourse to God. It will be argued that Einstein’s explanation has overlooked the fact that he cannot explain the belief in “The Beyond” itself. That people appeal to “The Beyond” to explain experiences they cannot understand presupposes that they already believe that there is a “Beyond”. Where does this belief in “The Beyond” come from? Drawing on the thoughts of Emmanuel Levinas, the author will show that it is moral consciousness, conscience, that opens humans’ horizon to “The Beyond”. The article concludes by pointing to the fact that both the emergence of the universe and the development of life on earth are extremely improbable. This improbability, however, would disappear if the universe were created by God. Abstrak Tulisan ini mempertanyakan pernyataan termasyhur Einstein bahwa Allah adalah ungkapan kelemahan manusia dan agama tak lain merupakan penjelmaan takhayul primitif. Dibenarkan bahwa perkembangan-perkembangan di alam raya dapat dijelaskan dengan hukum alam, bukan dengan campur tangan Allah. Tulisan ini fokus pada pengandaian dalam argumentasi Einstein, yaitu bahwa kepercayaan kepada “Yang-Di-Seberang“ merupakan penjelasan manusia atas pengalaman-pengalaman yang tidak/belum dapat mereka jelaskan. Namun, bahwa manusia mengacu kepada “Yang-Di-Seberang“ mengandaikan bahwa ia sudah percaya pada adanya “Yang-Di-Seberang“. Dari mana kepercayaan itu? Dengan bertolak dari pemikiran Levinas, akan ditunjukkan bahwa kiranya kesadaran moral, hati nurani, itulah yang membuka horizon manusia akan “Yang-Di-Seberang“. Sebagai penutup akan ditunjukkan fakta bahwa munculnya alam raya dan perkembangan kehidupan di bumi secara ekstrem tidaklah probabel. Andai kata alam raya ini diciptakan oleh Allah, ketidakprobabelan itu hilang. Kata-kata kunci: ateisme, Einstein, Levinas, Yang-di-Seberang, hati nurani, probabilitas